2010
DOI: 10.3354/meps08755
|View full text |Cite
|
Sign up to set email alerts
|

Particle capture mechanisms in suspension-feeding invertebrates

Abstract: A large number of suspension-feeding aquatic animals (e.g. bivalves, polychaetes, ascidians, bryozoans, crustaceans, sponges, echinoderms, cnidarians) have specialized in grazing on not only the 2 to 200 µm phytoplankton but frequently also the 0.5 to 2 µm free-living bacteria, or they have specialized in capturing larger prey, e.g. zooplankton organisms. We review the different particle capture mechanisms in order to illustrate the many solutions to the common problem of obtaining nourishment from a dilute su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
179
1
4

Year Published

2012
2012
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 205 publications
(191 citation statements)
references
References 243 publications
(388 reference statements)
2
179
1
4
Order By: Relevance
“…However, the difference in CR of Didemnum sp., which indicated a higher CR for cyanobacteria than for nanoeukaryotes, is a surprising finding and is difficult to interpret. This result is even more surprising since no specific organ has been described for ascidians that allows for the sorting of particles (Riisgård & Larsen 2010). However, the same result was obtained on 2 different dates.…”
Section: Valuementioning
confidence: 62%
See 1 more Smart Citation
“…However, the difference in CR of Didemnum sp., which indicated a higher CR for cyanobacteria than for nanoeukaryotes, is a surprising finding and is difficult to interpret. This result is even more surprising since no specific organ has been described for ascidians that allows for the sorting of particles (Riisgård & Larsen 2010). However, the same result was obtained on 2 different dates.…”
Section: Valuementioning
confidence: 62%
“…The differences of SIR between pearl oysters and ascidians could thus be explained by a differential use of phytoplanktonic food sources, according to particle size. These differences are likely related to differences in sorting abilities between bivalves and ascidians, with bivalves being well known for their ability to sort and select food particles, in contrast to ascidians (Ward & Shumway 2004, Riisgård & Larsen 2010. Even if there is a diet overlap for some food items, the similar growth rate measured for pearl oysters in the presence or absence of epibionts (Lacoste et al 2014b) indicated that biofouling does not prevent pearl oysters from accessing sufficient food resources to support their growth.…”
Section: Intra-and Interspecific Variations In Sirsmentioning
confidence: 99%
“…Porcelain crabs, barnacles, calanoid copepods, and most branchiopods use filter setae to capture particles (Riisgard and Larsen, 2010). On the basis of their size and structure, filter setae only capture particles of certain sizes, shapes, and surface chemistry (Palmer et al, 2004), making them more selective than pump systems.…”
Section: Discussionmentioning
confidence: 99%
“…Oysters, like many bivalves, feed using laterofrontal cirri to create currents, or a pump system, that directs food particles to the mouth (Riisgard and Larsen, 2010). Crassostrea virginica is able to consume suspended particles 1-12 mm in diameter and optimally consumes those between 3 mm and 4 mm (Haven and Morales-Alamo, 1970).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation